Transformation of Kyai's Democratic Leadership in Maintaining the Existence of Ibnul Qoyyim Putri Islamic Boarding School Berbah Sleman Yogyakarta - Rubini (STAI Terpadu Yogyakarta, 2024)
The purpose of this study is to understand the democratic leadership transformation efforts made by Kyai in increasing the existence of the Ibnul Qoyyim Putri Islamic boarding school in Berbah, Sleman Yogyakarta. This research employs a qualitative approach with a case study design, allowing the researcher to explore the context and dynamics of democratic leadership at Ibnul Qoyyim Putri Islamic Boarding School. The research subjects include the chief of the Islamic boarding school (Kyai), the head of the madrasah, teachers, educational staff, employees, students, and parents of students. Data collection techniques involve interviews, observations, and documentation. The analysis is conducted through several steps: data transcription, coding, thematic analysis, and interpretation. To ensure data validity, the researcher will use data triangulation by comparing information from various sources and methods and perform member checking by providing preliminary results to several respondents for confirmation and feedback. The findings indicate that transformation of the democratic leadership of the Kyai in maintaining the existence of the Ibnul Qoyyim Putri Islamic boarding school in Berbah, Sleman, Yogyakarta brings significant benefits to the existence and development of the boarding school. This democratic leadership is characterized by a deliberative system, where the Kyai shares decision-making responsibilities with staff and employees, delegates authority, and facilitates reciprocal communication. Although Kyai is not directly involved in daily operations, the provided guidance and periodic control demonstrate a collaborative and trusting attitude. This leadership style promotes active participation in decision-making and has positive impacts, including increased engagement and motivation, character development, and community strengthening.